2015
DOI: 10.3329/baj.v17i1.23681
|View full text |Cite
|
Sign up to set email alerts
|

Variations in salinity tolerance of selected mango rootstocks

Abstract: An experiment was conducted at the Germplasm Centre, Department of Horticulture, Patuakhali Science and Technology University (PSTU) during the period from July 2011 to March 2013 to study the performance of selected mango rootstocks in the saline area in Bangladesh. The experiment consisted of four mango rootstock lines collected from Rangpur, Dumki, Khulna and Kuakata, and five salinity treatments namely control (0 dSm-1), low (4 dSm-1), medium (6 dSm-1), high (8 dSm-1) and very high (10 dSm-1). A two factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In our results, under non salty water irrigation, there weren't any injury symptoms on leaves but with increasing salinity levels of irrigation water from 1750ppm to 3500ppm, the percentage of injured leaves and injured seedlings increased in both cultivars (Table 7). This is in accordance with Roy et al, (2015), Rashedy & Abd Allatif (2017) and Deivasigani et al, (2018), they reported that survival percentage of seedlings decreased with raising salinity level. With olive seedlings, Kchaou et al, (2010) reported that leaf drop started from 60 days after applying high salty water and this phenomenon differed among olive cultivars.…”
Section: Discussionsupporting
confidence: 91%
“…In our results, under non salty water irrigation, there weren't any injury symptoms on leaves but with increasing salinity levels of irrigation water from 1750ppm to 3500ppm, the percentage of injured leaves and injured seedlings increased in both cultivars (Table 7). This is in accordance with Roy et al, (2015), Rashedy & Abd Allatif (2017) and Deivasigani et al, (2018), they reported that survival percentage of seedlings decreased with raising salinity level. With olive seedlings, Kchaou et al, (2010) reported that leaf drop started from 60 days after applying high salty water and this phenomenon differed among olive cultivars.…”
Section: Discussionsupporting
confidence: 91%
“…Master-royal mango cultivar in combination with soil potting media of composition of Soil: Sand: FYM (2:1:1) resulted in higher number of leaves [37]. Many researchers reported similar findings on different mango cultivars [17,42,43]. High soil nutrient availability in the potting media can improve nutrient availability and water for growth of mango seedlings [31].…”
Section: Number Of Leavesmentioning
confidence: 99%
“…The decline in vegetative growth in this study correlated with increasing levels of salinity agrees with results of Duran Zuazo et al (2003), on Osteen cultivar, grafted onto Gomera-3 and Gomera-1 rootstocks, Pandey (2013) on two mango genotypes viz., Kurukkan and Olour, Roy et al (2014) on four mango rootstock lines collected from Kuakata, Khulna, Dumki, and Rangpur, and (Rashedy and Abd Allatif, 2017) on Ewais, Hindi Besinnara, Misk, Zebda, Sukkary, and Golek cvs. They reported that the saline conditions reduced the number of leaves, stem diameter, plant height, and leaves fresh and dry weight of plants compared to the control treatment.…”
Section: Vegetative Growthmentioning
confidence: 99%